Pentingnya Keamanan Data Dalam Era Digital: Refleksi Terhadap Serangan Hacker Pada Pusat Data Nasional Indonesia - Rafli Al Ihsan; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
In the digital era, data security has become a crucial issue for many countries, including Indonesia, especially after the hacker attack on Indonesia's National Data Center exposed the vulnerability of the system and its impact on national security and public trust. This journal aims to investigate the importance of data security in the digital era with a focus on the hacker attack that occurred on the PDN. This research uses the literature study method to explore the importance of data security, analyze the level of vulnerability of the National Data Center to cyberattacks, its impact on government stability and operations, and formulate strategies and policies that can be implemented to strengthen data defense. The results show that in addition to improved security technology, strict policies and good human resource education, inter-agency cooperation and international collaboration are also very important in building a resilient security system.